ANALYZING THE VALUE OF INFRASTRUCTURE COMPANIES ON DAFTAR EFEK SYARIAH THROUGH FINANCIAL PERFORMANCE AND CORPORATE SOCIAL RESPONSIBILITY (CSR) - Galuh Tri Pambekti (Journal of Accounting and Finance, 2022)
This study aims to obtain empirical evidence about the effect of Financial Performance and Corporate Social Responsibility (CSR) on Corporate Values in Construction Companies. The independent variables used are Financial Performance and Corporate Social Responsibility (CSR). Meanwhile, the dependent variable used is Corporate Value. The population in this study are construction service companies listed on the Indonesia Stock Exchange in 2009-2017. Samples were collected by purposive sampling method. The number of companies used as the sample of this research are 4 construction service companies. The method of analysis of this study uses multiple linear regression. In this study, financial performance variables are proxied by Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA), Capital Adequacy Ratio (CAR), and Corporate Social Responsibility (CSR) variables proxied by disclosure index Corporate Social Responsibility Disclosure. The results of this study indicate that partially, Non Performing Loans (NPL) have a significantly negative effect on  Company Value (Y), Loan to Deposit Ratio (LDR) has a significantly positive effect on Company Value (Y), influential Return on Assets (ROA) positively significant towards Corporate Value (Y), Capital Adequacy Ratio (CAR) has a significantly positive effect on Company Value (Y), Corporate Social Responsibility (CSR) has a significantly positive effect on Corporate Value (Y). Simultaneously, all independent variables affect the dependent variable.